Pemanfaatan Daun Sirih sebagai Biolarvasida Alami Pengganti Larvasida Sintetis - Santoso, Adi; Salsabila, Puti Athirah; Amellya, Risnanda Putri; Puspitasari, Muthia Fahriyah; Azzahra, Fatimah; Anggraeni, Fahrida Noor; Aulia, Amanda Karismatul; Kiswanti, Nafisyah; Wibowo, Rahmada Yasmin Ari (UNEJ e-Proceeding, 2023)
Background: The application of synthetic pesticides has risks and negative impacts on the environment, to reduce these risks it is necessary to introduce the application of environmentally friendly plant-based pesticides but does not exclude the main objective of eradicating Aedes aegeypti and Aedes albopictus mosquito larvae. Betel leaf (Paper berle L.) is a plant that has a toxic substance for insects, especially mosquito larvae. Betel leaves contain alkaloid compounds and other compounds such as essential oils, cineol and tanning substances. Methods: This research uses the observation or field research method by going directly to the community and preparing BIOSMO products and then socializing them by providing product samples and distribution of pre-tests and post-tests before and after the delivery of innovations to the community in Suci Village, Panti District, Jember Regency. Results: The results obtained from this activity are a natural biolarvicidal product from betel leaf extract and increased abilities obtained from the results of pre-test and post-test distribution before and after delivering innovations to the community in Suci Village, Panti District, Jember Regency. Conclusion: BIOSMO (Biolarvasida Betel Mosquito) is a natural biolarvicidal product used to eradicate mosquito larvae. This product utilizes dried green betel leaves as its main raw material, which is of course environmentally friendly and can reduce the use of abate.Keywords: Larvicidal dengue fever, biolarvicidal, biosmo, betel, abate.